TEMPORAL BEHAVIOR OF MARINE LANDING IN KARNATAKA.II.SEASONAL PATTERNS - GADAGKAR, SUDHINDRA R; SUNDARARAJ, N (Fishery Technology, 2017)
Seasonal patterns of 21 fisheries in Karnataka (after isolation from time-series components) are presented. Depending on the pattern of seasonal fluctuation in landings, 19 fisheries have been grouped into five patterns, A, B, C, D and E. Ribbon fishes and ’other clupeids’ did not exhibit any significant seasonal pattern. Pattern A with highest landings in the 4th quarter (October to December), followed by the 1, 2 TEand 3 quarters, is the most common in 10 species/groups (comprising 78% of the total landings). Harmonic analysis has been carried out using the seasonal indices.